G2G interaction model of information sharing among local agencies based on phenomenology approach: Dhi-qar province employees’ viewpoints - Al-Khafaji, Nassir Jabir Farhan (2016)
The exchange of information electronically has help local agencies to increase their productivity and performance. At the same time, it improves the process of policy-making by providing better public services to citizens. However, only a few studies that examine the factors influencing the electronic interaction among local agencies in developing countries, including in Iraq. In fact, government agencies usually rely on information provided by other government agencies, making the electronic interactions crucial for effective inter-organizational operations management in the government. This study aims to determine the factors affecting the interaction among local agencies in Dhi-Qar, Iraq. Thus, it proposes a government-to-government (G2G) interaction model among local agencies from the environmental, organizational, and technological contexts, using phenomenological approach based on the Diffusion of Innovation and Social Exchange theories. Data were collected in two phases. First, a series of interviews with local egovernment employees were carried out to discover the factors that influence the G2G interaction in Dhi-Qar, Iraq. Later, another series of semi-structured interviews focusing on extracting the main issues that influence G2G interaction was followed. The collected data were validated through triangulation and member checking. A case study was used to confirm the findings. The study has discovered the factors that influence the electronic interaction among local agencies in Dhi-Qar. The factors are benefits, compatibility, complexity, costs, information security, inter-agency trust, internal resistance to change, information technology (IT) capability, legislation, physical security, and top management support. Based on these factors, the government-to-government interaction model (G2GIM) is proposed. This model can be applied to different local agencies in implementing e-government projects.